2021
DOI: 10.1007/s11814-021-0870-9
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic pyrolysis of linear low-density polyethylene using recycled coal ash: Kinetic study and environmental evaluation

Abstract: Catalytic pyrolysis offers a sustainable route to convert plastic wastes into fuel. We investigated the catalytic performance of coal ash (fly and bottom ash) at blending ratio of 5 wt%, and 15 wt% during pyrolysis of linear lowdensity polyethylene (LLDPE). The influence on activation energy and oil was characterized via thermogravimetric analyzer (TGA) and gas chromatography-mass spectrometry (GC-MS). Results have shown that 15 wt% bottom ash exhibited higher catalytic activity. The activation energy estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Bu et al (2019) [ 29 ] presented the kinetic parameters for orders 1, 2, and 3. Lai et al (2021) [ 30 ] and Li et al (2022) [ 31 ] used only the first order of CR because it is considered as the main mechanism. Patidar et al (2022) [ 32 ] revealed that the diffusion model was best suited to reflect the degradation process using the CR method.…”
Section: Resultsmentioning
confidence: 99%
“…Bu et al (2019) [ 29 ] presented the kinetic parameters for orders 1, 2, and 3. Lai et al (2021) [ 30 ] and Li et al (2022) [ 31 ] used only the first order of CR because it is considered as the main mechanism. Patidar et al (2022) [ 32 ] revealed that the diffusion model was best suited to reflect the degradation process using the CR method.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the low value of the activation energy would help to run experiments at lower temperatures. Lai et al (2021) [ 18 ] examined the performance of coal ash (fly and bottom ash) with different blending ratios for the catalytic pyrolysis of LLDPE. They showed that 15 wt% bottom ash had higher effect on catalytic activity compared to 15 wt% fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…67 Subsequently, basic catalyst could promote the beta scission of unstable carbanions and get alkenes and smaller carbanions. 68 And smaller carbanions would proceed with the same cracking reaction as well. 69 Future study about the promotion of beta scission over basic catalyst is necessary, while it is suggested by Fu et al ( 2016) 70 that the presence of alkaline metals could change the electron density of the carbon atom and weaken the C−C bond.…”
Section: Petroleum Refineriesmentioning
confidence: 99%
“…While the difference is the hydrocarbon molecules after hydrogen abstraction would form carbanions . Subsequently, basic catalyst could promote the beta scission of unstable carbanions and get alkenes and smaller carbanions . And smaller carbanions would proceed with the same cracking reaction as well .…”
Section: Basic Catalyst For Catalytic Cracking In Petroleum Refineriesmentioning
confidence: 99%